Business Intelligence Design for the Purchasing and Selling Decision Making - Murnawan (International Journal of Psychosocial Rehabilitation, 2020)
The role of information technology in business enterprise processes is increasingly inseparable. The role of information technology as a tool for the performance of a company or organization in terms of providing the information needed in business operations, including management information, corporate critical data, the preparation of effective reports, and increasing the effectiveness of decision-making. Business intelligence (BI) is a tool that can support data processing to produce quality information and analyze information to produce knowledge that can support the decision-making process. BI Systems is a term generally used for applications and technologies that are used to help BI activities, such as collecting data, providing access, and analyzing data, as well as information on company performance. Then, from the board, the executive can easily understand it and draw a conclusion from all the data for the decision-making process, especially in sales and purchases. From the application of the control panel, the corporation can also make a conclusion about the forecast function, for example, which product is the most sold, which region ordered the most products, etc., which can help the executive to make a decision.